Sources of information and their impact on parents' vaccination decisions: a systematic review - Mahmud, Aidalina; K. M., Damyanthi (Community Health Society Malaysia, 2014)
Background: The frequency and manner of which health information are used is influenced by the sources. These sources may be seen as having different credibility among various sub-groups of the population. Such credibility in turn can have a marked impact on the acceptance and trust of the population on a specific source of information.